2014
DOI: 10.1002/ana.24067
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen for blast‐related postconcussion syndrome: Three‐month outcomes

Abstract: Using a randomized control trial design and analysis including a sham, results showed no evidence of efficacy by 3 months post-compression to treat the symptomatic, cognitive, or behavioral sequelae of PCS after combat-related mTBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 58 publications
6
61
0
Order By: Relevance
“…Five relevant studies [5][6][7][8][9] were found and analyzed as shown in Table 1 (based on Levels of Evidence, Centre for Evidence Based Medicine, 2009). Wolf et al 5 concluded that there was no effect on postconcussion symptoms after an HBOT treatment (2.4 atmospheres absolute [ATA] breathing 100% oxygen) compared with the sham group (1.3 ATA breathing 21% oxygen).…”
Section: Results Of Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…Five relevant studies [5][6][7][8][9] were found and analyzed as shown in Table 1 (based on Levels of Evidence, Centre for Evidence Based Medicine, 2009). Wolf et al 5 concluded that there was no effect on postconcussion symptoms after an HBOT treatment (2.4 atmospheres absolute [ATA] breathing 100% oxygen) compared with the sham group (1.3 ATA breathing 21% oxygen).…”
Section: Results Of Searchmentioning
confidence: 99%
“…The treatment parameters and results were similar, with subsequent studies measuring eye movements 7 and 3-month outcomes. 8 Boussi-Gross et al 9 concluded that HBOT treatment (1.5 ATA breathing 100% oxygen) can be used to improve quality of life and cognitive function in patients suffering from postconcussion syndrome.…”
Section: Results Of Searchmentioning
confidence: 99%
See 3 more Smart Citations